A versatile platform for surface modification of microfluidic droplets. Issue 4 (3rd February 2017) - Li, Mingqiang; Jiang, Weiqian; Chen, Zaozao; Suryaprakash, Smruthi; Lv, Shixian; Tang, Zhaohui; Chen, Xuesi; Leong, Kam W.
Abstract : Droplet surface decoration: method for surface modification of microfluidic emulsions, with precise control over droplet surface properties. Abstract : To advance emulsion droplet technology, we synthesize functional derivatives of Pluronic F127 that can simultaneously act as surfactants and as reactive sites for droplet surface decoration. The amine-, carboxyl-, N -hydroxysuccinimide ester-, maleimide- and biotin-terminated Pluronic F127 allows ligand immobilization on single-emulsion or double-emulsion droplets via electrostatic adsorption, covalent conjugation or site-specific avidin–biotin interaction.